A New Computational Method for Optimizing Nonlinear Impulsive Systems - Lin, Qun; Loxton, Ryan; Teo, Kok Lay; Wu, Yong Hong (WATAM Press, 2011)
In this paper, we consider a system that evolves by switching between several subsystems of ordinary differential equations. The switching mechanism is this system induces an instantaneous change in the system's state, which can be controlled through a set of decision parameters. We develop a new computational method, based on nonlinear programming, for optimizing the system parameters and the subsystem switching times. We then successfully apply this method to two interesting examples.